Investigation of suicide rates for mental disorders in OECD countries by gender and time - Esra Uslu (Genel Tıp Dergisi)
Purpose: The aim of the study is to evaluate the suicide rate in individuals with mental disorders in terms of gender and time. Design and Methods: In this study, a retrospective research design was used and secondary data were used. The sample of the study consisted of OECD countries. Findings: Although the suicide rate is higher in men than in women, there is no statistical difference (p>0.05). Suicide rate increases during hospitalization, 30 days after discharge, and in follow-ups within one year (p<0.001). Conclusion: It is believed that the results will guide healthcare professionals in diagnosing suicide risk and planning related actions (policy and interventions).